Intravesical nadofaragene firadenovec gene therapy for BCG-unresponsive non-muscle-invasive bladder cancer: a single-arm, open-label, repeat-dose clinical trial. Issue 1 (January 2021) - Boorjian, Stephen A; Alemozaffar, Mehrdad; Konety, Badrinath R; Shore, Neal D; Gomella, Leonard G; Kamat, Ashish M; Bivalacqua, Trinity J; Montgomery, Jeffrey S; Lerner, Seth P; Busby, Joseph E; Poch, Michael; Crispen, Paul L; et al.
Summary: Background: BCG is the most effective therapy for high-risk non-muscle-invasive bladder cancer. Nadofaragene firadenovec (also known as rAd-IFNa/Syn3) is a replication-deficient recombinant adenovirus that delivers human interferon alfa-2b cDNA into the bladder epithelium, and a novel intravesical therapy for BCG-unresponsive non-muscle-invasive bladder cancer. We aimed to evaluate its efficacy in patients with BCG-unresponsive non-muscle-invasive bladder cancer. Methods: In this phase 3, multicentre, open-label, repeat-dose study done in 33 centres (hospitals and clinics) in the USA, we recruited patients aged 18 years or older, with BCG-unresponsive non-muscle-invasive bladder cancer and an Eastern Cooperative Oncology Group status of 2 or less. Patients were excluded if they had upper urinary tract disease, urothelial carcinoma within the prostatic urethra, lymphovascular invasion, micropapillary disease, or hydronephrosis. Eligible patients received a single intravesical 75 mL dose of nadofaragene firadenovec (3 × 10 11 viral particles per mL). Repeat dosing at months 3, 6, and 9 was done in the absence of high-grade recurrence. The primary endpoint was complete response at any time in patients with carcinoma in situ (with or without a high-grade Ta or T1 tumour). The null hypothesis specified a complete response rate of less than 27% in this cohort. Efficacy analyses were done on the per-protocol population, to include only patients strictly meeting the BCG-unresponsive definition. Safety analyses were done in all patients who received at least one dose of treatment. The study is ongoing, with a planned 4-year treatment and monitoring phase. This study is registered with ClinicalTrials.gov, NCT02773849 . Findings: Between Sept 19, 2016, and May 24, 2019, 198 patients were assessed for eligibility. 41 patients were excluded, and 157 were enrolled and received at least one dose of the study drug. Six patients did not meet the definition of BCG-unresponsive non-muscle-invasive bladder cancer and were therefore excluded from efficacy analyses; the remaining 151 patients were included in the per-protocol efficacy analyses. 55 (53·4%) of 103 patients with carcinoma in situ (with or without a high-grade Ta or T1 tumour) had a complete response within 3 months of the first dose and this response was maintained in 25 (45·5%) of 55 patients at 12 months. Micturition urgency was the most common grade 3–4 study drug-related adverse event (two [1%] of 157 patients, both grade 3), and there were no treatment-related deaths. Interpretation: Intravesical nadofaragene firadenovec was efficacious, with a favourable benefit:risk ratio, in patients with BCG-unresponsive non-muscle-invasive bladder cancer. This represents a novel treatment option in a therapeutically challenging disease state. Funding: FKD Therapies Oy.